Parafibromin mutations in hereditary hyperparathyroidism syndromes and parathyroid tumours. - Bradley, K; Cavaco, B; Bowl, MR; Harding, B; Cranston, T; Fratter, C; Besser, G; Conceição Pereira, M; Davie, M; Dudley, N; Leite, V; Sadler, G; et al. (2006)
OBJECTIVE: To investigate two patients with the hyperparathyroidism-jaw tumour (HPT-JT) syndrome and three patients with familial isolated hyperparathyroidism (FIHP), together with 31 parathyroid tumours (2 HPT-JT, 2 FIHP and 27 sporadic) for HRPT2 mutations. The HPT-JT syndrome and FIHP are autosomal dominant disorders that may be caused by abnormalities of the HRPT2 gene, located on chromosome 1q31.2. HRPT2 encodes a 531 amino acid protein, parafibromin, which interacts with human homologues of the yeast Paf1 complex. DESIGN: Leukocyte and tumor DNA was used with HRPT2-specific primers for polymerase chain reaction amplification of the 17 exons and their splice junctions, and the DNA sequences of the polymerase chain reaction products determined. RESULTS: Three heterozygous germline HRPT2 mutations, two in HPT-JT and one in FIHP patients, were identified. These consisted of one 1-bp duplication (745dup1bp), 1 nonsense (Arg234Stop) and 1 missense (Asp379Asn) mutation. One parathyroid tumour from an FIHP patient was demonstrated to harbour a germline deletion of 1 bp together with a somatic missense (Leu95Pro) mutation, consistent with a 'two-hit' model for hereditary cancer. The 27 sporadic benign parathyroid tumours did not harbour any HRPT2 somatic mutations. Six HRPT2 polymorphisms with allele frequencies ranging from 2% to 15% were detected. CONCLUSIONS: Our results have identified three novel HRPT2 mutations (two germline and one somatic). The Asp379Asn mutation is likely to disrupt interaction with the human homologue of the yeast Paf1 complex, and the demonstration of combined germline and somatic HRPT2 mutations in a parathyroid tumour provide further evidence for the tumour suppressor role of the HRPT2 gene.